2006
DOI: 10.1016/j.jmb.2006.06.079
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of an Active Form of Human MMP-1

Abstract: The extracellular matrix is a dynamic environment that constantly undergoes remodelling and degradation during vital physiological processes such as angiogenesis, wound healing, and development. Unbalanced extracellular matrix breakdown is associated with many diseases such as arthritis, cancer and fibrosis. Interstitial collagen is degraded by matrix metalloproteinases with collagenolytic activity by MMP-1, MMP-8 and MMP-13, collectively known as the collagenases. Matrix metalloproteinase 1 (MMP-1) plays a pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
123
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(129 citation statements)
references
References 32 publications
3
123
0
3
Order By: Relevance
“…Comparison of the crystal structure of proMMP-1 (29) with the structure of the activated form of MMP-1(E200A) (6,7) suggested that the Cat-Hpx linker region confers interdomain flexibility. Such flexing was further demonstrated for MMP-1 by NMR and small angle X-ray scattering studies (40,41) and seems to be a common property of MMPs (42,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of the crystal structure of proMMP-1 (29) with the structure of the activated form of MMP-1(E200A) (6,7) suggested that the Cat-Hpx linker region confers interdomain flexibility. Such flexing was further demonstrated for MMP-1 by NMR and small angle X-ray scattering studies (40,41) and seems to be a common property of MMPs (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…It consists of an N-terminal catalytic (Cat) domain containing an active-site zinc ion and a C-terminal hemopexin (Hpx) domain comprised of a four-bladed β-propeller, which are connected by a linker region (6,7). Although the Cat domain can cleave a number of noncollagenous proteins including heat-denatured collagen (gelatin), its activity on native triplehelical collagen is negligible.…”
mentioning
confidence: 99%
“…3 Ribbon diagram representation of the full-length MMP-1 structure. This figure was modeled after the X-ray structure of porcine synovial collagenase [29]. Mutated amino acids Val268, Gly272, and Lys277 of the hinge region are shown.…”
Section: Site-directed Mutants Of Mmp-1mentioning
confidence: 99%
“…Since physiological collagenolysis is crucial for several biological processes, such as tissue repair and remodeling, angiogenesis, and wound healing [3,21], and collagenases are the main MMPs involved in collagen turnover and remodeling [22][23][24], a clarification of the mechanism of processing of the triple helix by collagenases is of the utmost importance. Structural data on fibrillar collagen I [25][26][27] indeed have shown that, on the basis of the available three-dimensional structures of collagenases [28,29], the triple-helical structural assembly does not allow collagen I to come into close contact with the catalytic site of collagenases. Therefore, a more complex mechanism of substrate recognition must be postulated, where an exosite topologically distinct from the active site interacts with the substrate (likely through the hemopexin-like domain in collagenases; see [14]) with a very limited alteration of the triple-helical arrangement of collagen I [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…1) (10,11), and anti-GBD antibodies inhibit collagen organization in fibroblast cultures (12). Similarly, experiments in cultures have identified the collagenase/ MMP-1 (13) cleavage site in type I collagen as important for FN-mediated attachment of fibroblasts to collagen ECM (14). Peptides spanning that region (15) or MMP-1 cleavage at this site (6) inhibit attachment.…”
mentioning
confidence: 98%